The enterocyte-associated intestinal microbiota of breast-fed infants and adults responds differently to a TNF-α-mediated pro-inflammatory stimulus. - Manuela Centanni (Public Library of Science (PLoS), 2013)
Co-evolved as an integral component of our immune system, the gut microbiota provides specific immunological services at different ages, supporting the immune education during our infancy and sustaining a well-balanced immunological homeostasis during the course of our life. In order to figure out whether this involves differences in the microbial groups primarily interacting with the host immune system, we developed a non-invasive HT29 cell-based minimal model to fingerprint the enterocyte-associated microbiota fraction in infants and adults. After depicting the fecal microbial community of 12 breast-fed infants and 6 adults by 16S rDNA amplicon pools 454 pyrosequencing, their respective HT29 cell-associated gut microbiota fractions were characterized by the universal phylogenetic array platform HTF-Microbi.Array, both in the presence and absence of a tumor necrosis factor-alpha (TNF-α)-mediated pro-inflammatory stimulus. Our data revealed remarkable differences between the enterocyte-associated microbiota fractions in breast-fed infants and adults, being dominated by Bifidobacterium and Enterobacteriaceae the first and Bacteroides-Prevotella and Clostridium clusters IV and XIVa the second. While in adults TNF-α resulted in a profound impairment of the structure of the enterocyte-associated microbiota fraction, in infants it remained unaffected. Differently from the adult-type gut microbial community, the infant-type microbiota is structured to cope with inflammation, being co-evolved to prime the early immune response by means of transient inflammatory signals from gut microorganisms.